2015
DOI: 10.1158/0008-5472.can-14-2376
|View full text |Cite
|
Sign up to set email alerts
|

MDSC and TGFβ Are Required for Facilitation of Tumor Growth in the Lungs of Mice Exposed to Carbon Nanotubes

Abstract: During last decades, changes have been observed in the frequency of different histological subtypes of lung cancer - one of the most common causes of morbidity and mortality - with a declining proportion of squamous cell carcinomas and an increasing proportion of adenocarcinomas, particularly in developed countries. This suggests the emergence of new etiological factors and mechanisms including those defining the lung microenvironment promoting tumor growth. Assuming that the lung is the main portal of entry f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…Increasing evidence suggests that certain types of CNTs are carcinogenic7891011123940. Although the mechanism underlying this carcinogenicity remains incompletely understood, an induction of CSCs by CNTs has been implicated1314.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence suggests that certain types of CNTs are carcinogenic7891011123940. Although the mechanism underlying this carcinogenicity remains incompletely understood, an induction of CSCs by CNTs has been implicated1314.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with the earlier reports showing the modulation of the tumor microenvironment by CNTs that promotes tumor growth. For example, a single pharyngeal aspiration of SWCNT in mice was shown to induce an accumulation of myeloid-derived suppressor cells in the lungs that resulted in host immunosuppression and lung carcinoma acceleration78. The detection of CNT-induced CAF-like cells could be beneficial over the previously reported CNT-induced lung epithelial cell transformation in view of its rapid response to CNT stimuli (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was mediated by increased local and systemic accumulation of MDSCs [94]. Subsequent studies further revealed that in vivo exposure to CNT rendered lung MDSCs susceptible to tumor-induced expression of TGFβ, which was responsible for the inhibition of T cell activity by MDSCs [95]. Dajon et al, using a murine model of lung adenocarcinoma, found that stimulation of Toll-like receptor 7 (TLR7) expressed by adenocarcinoma cells modulated the immune infiltrate, leading to a significant expansion of MDSCs that was associated with increased secretion of CCL2 and GM-CSF in the tumor microenvironment.…”
Section: Mdscs In Murine Models Of Lcmentioning
confidence: 99%
“…It was further found that MDSC-derived TGF-β signaling was critical to SWCNT-induced immunosuppression through the inhibition of T-cell activation and proliferation. 62 These findings could lead to the development of screening platforms for evaluating the CNT effects on tumor microenvironment.…”
Section: Carcinogenic Potential Of Cnts: In Vivo Assessmentmentioning
confidence: 99%